Airway Preparation Techniques for the Cervical Spine-Injured Football Player - Ray, Richard (1995)
Athletic health care professionals have been concerned about how to optimize the emergency care the cervical spine-injured football player receives on the field. Much of the discussion has centered on how to best expose and prepare the airway for rescue breathing in the quickest and safest manner possible. This study compared the time required and the extraneous motion induced at the cervical spine during three traditional and one new airway exposure and preparation technique. Twelve subjects wearing football helmets and shoulder pads were exposed to multiple trials of airway exposure via face mask repositioning using a manual screwdriver, power screwdriver, and the Trainer's Angel cutting device. Subjects also underwent airway preparation using the pocket mask insertion technique. Cervical spine motion was measured in two dimensions using an optoelectronic motion analysis system. Time and qualitative assessment were obtained through videotape analysis. Significant differences were found between the techniques with respect to time and cervical spine motion. The pocket mask allowed quicker activation of rescue breathing than the other three traditional techniques. There was no significant difference in the amount of extraneous motion induced at the cervical spine between the pocket mask, manual screwdriver, and power screwdriver techniques. The Trainer's Angel induced significantly more motion than the other three techniques in each of the four motions measured. Changes in traditional protocols used to treat cervical spine-injured football players on the field are recommended based on these data.